2011
DOI: 10.1021/es200413g
|View full text |Cite
|
Sign up to set email alerts
|

Microbially Mediated Abiotic Transformation of the Antimicrobial Agent Sulfamethoxazole under Iron-Reducing Soil Conditions

Abstract: Large quantities of antimicrobial agents used in livestock production are released to soils by land application of manure, but only limited information is available on mechanisms that contribute to antimicrobial fate in soils under variable biogeochemical conditions. Dissipation of the sulfonamide antimicrobial sulfamethoxazole was examined in soil microcosms incubated under different terminal electron-accepting conditions (aerobic, nitrate-reducing, Fe(III)-reducing, and sulfate-reducing). Somewhat unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 53 publications
5
63
0
Order By: Relevance
“…Different from sulfonamide compounds, whose degradation by pure bacterial cultures [47][48][49] and microbially mediated abiotic processes [50] have been reported, little is known about how microbial processes may transform tetracycline compounds. Several…”
Section: Discussionmentioning
confidence: 99%
“…Different from sulfonamide compounds, whose degradation by pure bacterial cultures [47][48][49] and microbially mediated abiotic processes [50] have been reported, little is known about how microbial processes may transform tetracycline compounds. Several…”
Section: Discussionmentioning
confidence: 99%
“…Measurements. Mineralization of 14 C-SMZ added to the microcosms was measured using NaOH traps at 3,7,14,21,28,35,42,49, and 56 days. Traps consisted of a 25-mL highdensity polyethylene vial glued to the inner surface of the jar and filled with 10 mL of 0.5 M NaOH.…”
Section: ■ Experimental Materials and Methodsmentioning
confidence: 99%
“…Abiotic transformation of the antibiotics might contribute a great to the degradation during composting. Research has demonstrated that high-organic soils/sediments tend to produce elevated levels of reduced sulfur compounds (e.g., bisulfide and polysulfides) and iron(II) species, which typically possess strong reducing capacity that may degrade veterinary antibiotics faster than microorganisms (Zeng et al 2011(Zeng et al , 2012Mohatt et al 2011). Similar to the manures, the SAs concentrations in the composts are lower than other TCs and FQs generally; however, SDZ in the soybean meal compost (SMC) and SCX in the rice husk compost (RHC) are prominent due to their significant higher level in the two composts.…”
Section: Veterinary Antibiotic Residues In Compostsmentioning
confidence: 99%